The COVID-19 pandemic and impact on breast cancer diagnoses: what happened in England in the first half of 2020 - Gathani, T; Clayton, G; MacInnes, E; Horgan, K (Nature Research, 2020)
Delays in cancer diagnosis and treatment due to the COVID-19 pandemic is a widespread source of concern, but the scale of the challenge for different tumour sites is not known. Routinely collected NHS England Cancer Waiting Time data were analysed to compare activity for breast cancer in the first 6 months of 2020 compared to the same time period in 2019. The number of referrals for suspected breast cancer was 28% lower (N = 231,765 versus N = 322,994), and the number of patients who received their first treatment for a breast cancer diagnosis was 16% lower (N = 19,965 versus N = 23,881). These data suggest that the number of breast cancers diagnosed during the first half of 2020 is not as low as initially feared, and a substantial proportion of the shortfall can be explained by the suspension of routine screening in March 2020. Further work is needed to examine in detail the impact of measures to manage the COVID-19 pandemic on breast cancer outcomes.